2007
DOI: 10.7589/0090-3558-43.4.576
|View full text |Cite
|
Sign up to set email alerts
|

Giardia Duodenalis Cysts Isolated From Wild Moose and Reindeer in Norway: Genetic Characterization by PCR-RFLP and Sequence Analysis at Two Genes

Abstract: ABSTRACT:There are few genotyping studies of Giardia duodenalis isolates from cervid hosts, although a previous study suggested that cervids may be a source of infection for humans and cattle. Giardia duodenalis isolates collected from wild moose (Alces alces) and reindeer (Rangifer tarandus) in Norway during 2002 and 2003 were characterized by polymerase chain reactionrestriction fraction length polymorphism (PCR-RFLP) at the b-giardin gene, and sequence analysis at both the b-giardin and glutamate dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
26
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 14 publications
2
26
0
2
Order By: Relevance
“…in red deer we found a Giardia isolate belonging to sub-assemblage aiii. the sequences of the studied molecular markers of the Giardia isolate detected in red deer were identical to the sequences of the same gene fragments of Giardia isolates from fallow deer, roe deer, moose and cat, which were earlier determined as the aiii sub-assemblage (van der Giessen et al 2006, Lalle et al 2007, Robertson et al 2007, Lebbad et al 2010. Previous studies indicated that Giardia isolates from the aiii sub-assemblage are specific for cervids.…”
Section: Fig 1 Phylogenetic Relationship Of 17mentioning
confidence: 52%
See 2 more Smart Citations
“…in red deer we found a Giardia isolate belonging to sub-assemblage aiii. the sequences of the studied molecular markers of the Giardia isolate detected in red deer were identical to the sequences of the same gene fragments of Giardia isolates from fallow deer, roe deer, moose and cat, which were earlier determined as the aiii sub-assemblage (van der Giessen et al 2006, Lalle et al 2007, Robertson et al 2007, Lebbad et al 2010. Previous studies indicated that Giardia isolates from the aiii sub-assemblage are specific for cervids.…”
Section: Fig 1 Phylogenetic Relationship Of 17mentioning
confidence: 52%
“…Whereas the role of pets and livestock in Giardia transmission has been studied intensively, the role of wild animals, particularly artiodactyls, has only recently been taken into consideration (trout et al 2003, lalle et al 2007, robertson et al 2007, Kutz et al 2008, Beck et al 2010. Wild cervids might play a significant role in contamination of the environment with Giardia cysts because large populations occur worldwide, they excrete a relatively large volume of faeces, and their feeding ranges usually overlap with cattle pastures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S3 and S4 in the supplemental material). Recently, a third subgroup within assemblage A, subgroup AIII, was identified and appears to be associated mostly with wild hoofed animals (37,219,282). It has significant sequence differences from subgroups AI and AII at all loci examined thus far ( Fig.…”
Section: Giardia Duodenalis Assemblagesmentioning
confidence: 97%
“…IFA coupled with immunomagnetic separation is currently one of the main methods to detect Giardia [23]. In addition, PCR-RFLP had been used frequently in field investigations on the occurrence of Giardia among primary school children [24] or in wild animals [25]. Therefore, the identification and characterization of new markers is needed to improve current detection methods for G. lamblia.…”
mentioning
confidence: 99%